Role of Rutin Nanoemulsion in Ameliorating Oxidative Stress: Pharmacokinetic and Pharmacodynamics Studies. (May 2020) - Sharma, Shrestha; Rabbani, Syed Arman; Narang, Jasjeet K; Hyder Pottoo, Faheem; Ali, Javed; Kumar, Shobhit; Baboota, Sanjula
Highlights: Pharmacokinetic and Pharmacodynamic studies were performed to assess the antioxidative potential of rutin nanoemulsion (NE) in Parkinson disease (PD). Oxidative stress studies (behavioural and biochemical) showed improved status in PD model for rutin NE as compared to pure rutin suspension. Higher cell mortality was observed with rutin NE than the pure drug. In vitro / In vivo studies were performed to assess the antioxidative potential of rutin nanoemulsion. Abstract: Parkinson's disease is caused due to free radical generation in dopamine neurons leading to oxidative stress induced damage. The aim of this work was to ameliorate the free radical induced oxidative stress in rats by using TPGS (Tocopheryl polyethylene glycol 1000 succinate) loaded rutin nanoemulsion after oral administration. For this purpose, pharmacokinetic and pharmacodynamics studies were performed in albino wistar rats. Various behavioural tests (photoactometer test, rota rod, akinesia and catalepsy) and biochemical estimations for determination of GSH, TBARS and SOD were carried out. The results showed an increase in relative bioavailability of rutin after oral administration of nanoemulsion as compared to pure drug suspension. The AUC and Cmax of rutin nanoemulsion after oral administration were 1.8-fold and 1.9-fold higher than those of drug suspension respectively. Pharmacodynamic studies have shown good results with the rutin nanoemulsion than pure drug suspension. The rats treated with the rutin nanoemulsion exhibited significantly greater locomotor activity, better muscle coordination and improvement in cataleptic behaviour than the normal and haloperidol-induced rats (p < 0.001).Treatment with rutin suspension and rutin nanoemulsion helped in improving the stressed condition by increasing the levels of GSH, SOD and decrease in MDA levels in the brain. Anticancer activity was observed in a dose-dependent manner from 1 to 100 μg/ml. IC50 values for rutin suspension and rutin NE were found to be 36.7 and 25.4 μg/ml respectively. The rutin nanoemulsion has proven to be beneficial in ameliorating oxidative stress.